"Turn-on" Pb2+ sensing and rapid detection of biothiols in aqueous medium and real samples. Issue 2 (14th November 2018) - Singh, Rupinder; Das, Gopal
Abstract : A single probe senses Pb 2+ in mixed aqueous medium and real samples followed by detection of a variety of biothiols in the same medium as well as in onion and garlic extract. Abstract : Detection of lead has continued to be of immense interest in the present industrial as well as environmental diaspora. To this end, we report a prudent Schiff base which enables the sensitive detection of Pb 2+ ions in mixed aqueous medium. The probe is afforded by simple synthetic and purification processes. Further, the probe employs simple mechanistic detection of Pb 2+ and also successively detects a host of biothiols. The sensor is also used to detect Pb 2+ ions in real water samples and consecutive detection of a variety of biothiols, including functionalized thiouracils, in onion and garlic extract. The fact that the Pb 2+ –L ensemble is 'non-selective' towards any particular thiol substituted analyte in real samples could as well prove to be an interesting contribution for chemical and biological detoxification processes.